Chorion patterning: a window into gene regulation and Drosophila species' relatedness. - Niepielko, M.G.; Marmion, R.A.; Kim, K.; Luor, D.; Ray, C.; Yakoby, N. (Molecular Biology and Evolution, 2014)
Changes in gene regulation are associated with the evolution of morphologies. However, the specific sequence information controlling gene expression is largely unknown and discovery is time and labor consuming. We use the intricate patterning of follicle cells to probe species' relatedness in the absence of sequence information. We focus on one of the major families of genes that pattern the Drosophila eggshell, the Chorion protein (Cp). Systematically screening for the spatiotemporal patterning of all nine Cp genes in three species (Drosophila melanogaster, D. nebulosa, and D. willistoni), we found that most genes are expressed dynamically during mid and late stages of oogenesis. Applying an annotation code, we transformed the data into binary matrices that capture the complexity of gene expression. Gene patterning is sufficient to predict species' relatedness, consistent with their phylogeny. Surprisingly, we found that expression domains of most genes are different among species, suggesting that Cp regulation is rapidly evolving. In addition, we found a morphological novelty along the dorsalmost side of the eggshell, the dorsal ridge. Our matrix analysis placed the dorsal ridge domain in a cluster of epidermal growth factor receptor associated domains, which was validated through genetic and chemical perturbations. Expression domains are regulated cooperatively or independently by signaling pathways, supporting that complex patterns are combinatorially assembled from simple domains.